2003
DOI: 10.1161/01.atv.0000091363.28501.84
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the HDL Receptor SR-BI on Lipoprotein Metabolism and Atherosclerosis

Abstract: Abstract-The scavenger receptor class B type I (SR-BI) was the first molecularly well-defined cell-surface HDL receptor to be described. SR-BI mediates selective HDL cholesterol uptake by formation of a productive lipoprotein/receptor complex, which requires specific structural domains and conformation states of apolipoprotein A-I present in HDL particles. SR-BI is abundantly expressed in several tissues, including the liver, where its expression is regulated by various mechanisms, including the transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
163
0
16

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(186 citation statements)
references
References 103 publications
(117 reference statements)
3
163
0
16
Order By: Relevance
“…1,2 In nonpolarized cells, namely macrophages and the hepatoma cell line Fu5AH, SR-BI expression either results in selective uptake of cholesterol, mainly from high-density lipoprotein (HDL), or in cholesterol efflux toward suitable acceptors. [3][4][5][6] In hepatocytes, which is a highly polarized cell type, SR-BI is the main receptor responsible for selective uptake of cholesterol from plasma HDL.…”
mentioning
confidence: 99%
“…1,2 In nonpolarized cells, namely macrophages and the hepatoma cell line Fu5AH, SR-BI expression either results in selective uptake of cholesterol, mainly from high-density lipoprotein (HDL), or in cholesterol efflux toward suitable acceptors. [3][4][5][6] In hepatocytes, which is a highly polarized cell type, SR-BI is the main receptor responsible for selective uptake of cholesterol from plasma HDL.…”
mentioning
confidence: 99%
“…5,6 In polarized cells, SR-BI is known to be localized largely at the plasma membrane, either apically (eg, enterocytes 7 ) or basolaterally (eg, hepatocytes 8 and MadinDarby canine kidney [MDCK] cells 9 ). Several reports have indicated that SR-BI functions as an endocytic receptor, particularly in polarized cells such as hepatocytes 8 and kidney (MDCK) 10 cells, and it has been proposed that selective lipid uptake from HDL occurs during SR-BI-mediated HDL recycling within cells.…”
mentioning
confidence: 99%
“…Общеизвестно, что эстрогены в пре-делах физиологической нормы существенно влия-ют на содержание липидов в крови, снижая уровень общего холестерина (ОХ) и липопротеидов низкой плотности (ЛПНП) и повышая уровень липопроте-идов высокой плотности (ЛПВП) [2]. Есть данные о том, что эстрогены непосредственно влияют на синтез липопротеидов в печени, увеличивая кон-центрацию холестерина (ХС) ЛПВП благодаря по-вышению синтеза апоА1, down-регуляции печеноч-ных скэвенджер-рецепторов типа В 1 класса (SRB-1) и снижению активности печеночной липазы [3]. Многими авторами [4][5][6] показаны антиоксидант-ные свойства эстрогенов.…”
unclassified